The impact of routine childhood immunization with higher-valent pneumococcal conjugate vaccines on antimicrobial-resistant pneumococcal diseases and carriage: a systematic literature review. (3rd October 2019) - Tin Tin Htar, Myint; van Den Biggelaar, Anita H.J.; Sings, Heather; Ferreira, Germano; Moffatt, Margaret; Hall-Murray, Cassandra; Verstraeten, Thomas; Gessner, Bradford D.; Schmitt, Heinz-Josef; Jodar, Luis
ABSTRACT: Introduction : The introduction of 7-valent pneumococcal conjugate vaccine (PCV7) in childhood immunization programs reduced antimicrobial-resistant pneumococcal infections by vaccine serotypes. However, emerging antimicrobial-resistant non-vaccine serotypes, particularly serotype 19A, attenuated the overall effect. In 2010, higher-valent PCVs became available containing serotypes that are prone to become antimicrobial-resistant, like serotype 7F in PCV10 and PCV13, and serotype 19A in PCV13. Areas covered : This review evaluated literature published between June 1, 2008 and June 1, 2017 reporting on the effect of PCV10 or PCV13 implementation in routine infant immunization schedules on antimicrobial-resistant invasive pneumococcal disease (IPD), otitis media (OM), and nasopharyngeal carriage (NPC) in children and adults. Expert opinion : In countries with relatively high prior pneumococcal antimicrobial resistance (AMR), PCV13 childhood vaccination programs have reduced antimicrobial-resistant IPD, OM, and NPC in children and IPD in adults. The effectiveness of PCV13 against serotype 19A is likely an important contributing factor. Only few studies have documented the impact of PCV10 on AMR. Multiple factors may influence observed decreases in pneumococcal AMR including antimicrobial stewardship, case definition, time since PCV10/13 introduction, and pre-PCV10/13 AMR levels. This review emphasizes the importance of including impact on AMR when evaluating the full public health of pneumococcal vaccination programs.